Unpacking the Link Between Work-Integrated Learning and Graduate Work Readiness: The Mediating Role of Student Commitment - Wisudani Rahmaningtyas; Anna Kania Widiatami (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to investigate the relationship between Work-Integrated Learning (WIL) and graduate work readiness, with a particular focus on the mediating role of student commitment as a key psychological mechanism in the learning process. Employing a quantitative cross-sectional design, data were collected from 367 undergraduate students enrolled in economics-related study programs at universities in Indonesia who had completed recognized Work-Integrated Learning (WIL) programs. Respondents were selected using proportional random sampling, and the data were analyzed using PLS-SEM. The findings reveal that WIL positively influences student commitment (β = 0.52) and work readiness (β = 0.21). Student commitment also demonstrates a positive effect on work readiness (β = 0.47) and partially mediates the relationship between WIL and work readiness (β = 0.24). These findings indicate a positive and significant relationship between experiential learning and learning outcomes, emphasizing that the effectiveness of WIL depends on students’ active psychological engagement. This study contributes to the existing literature by providing empirical evidence that student commitment serves as a critical pedagogical mechanism in transforming experiential learning into meaningful learning outcomes and offers practical implications for the design of WIL-based learning models that foster engagement, reflection, and sustainable competence development.